2017
DOI: 10.1002/jclp.22485
|View full text |Cite
|
Sign up to set email alerts
|

Professional Burnout, Early Maladaptive Schemas, and Physical Health in Clinical and Counselling Psychology Trainees

Abstract: The current study contributes to our understanding of the role of the US EMS in the evolution of burnout in trainees and has implications for the development of self-awareness training programs for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 77 publications
3
38
0
5
Order By: Relevance
“…Although willingness to help others and maintaining high standards are adaptive and essential to being an effective psychologist, our findings indicate that a significant proportion of psychologists endorse these EMS at a level that suggests excessive and maladaptive attitudes and behaviours associated with helping. These findings are consistent with preliminary research on trainee psychologists that found relatively high levels of self‐sacrifice and unrelenting standards EMS (Kaeding et al, ; Saddichha et al, ; Wyman, ) as well as broader theories about how psychologists become at risk of burnout. Much, Swanson, and Jazazewski () suggest that when personal needs are unmet and psychologists experience difficulty setting boundaries and limits with colleagues and patients, they may be more likely to experience symptoms of burnout.…”
Section: Discussionsupporting
confidence: 88%
“…Although willingness to help others and maintaining high standards are adaptive and essential to being an effective psychologist, our findings indicate that a significant proportion of psychologists endorse these EMS at a level that suggests excessive and maladaptive attitudes and behaviours associated with helping. These findings are consistent with preliminary research on trainee psychologists that found relatively high levels of self‐sacrifice and unrelenting standards EMS (Kaeding et al, ; Saddichha et al, ; Wyman, ) as well as broader theories about how psychologists become at risk of burnout. Much, Swanson, and Jazazewski () suggest that when personal needs are unmet and psychologists experience difficulty setting boundaries and limits with colleagues and patients, they may be more likely to experience symptoms of burnout.…”
Section: Discussionsupporting
confidence: 88%
“…Although the results found in the literature are consistent in showing the emotional difficulties faced by clinical psychology trainees, most of the studies have used qualitative and cross-sectional survey methods (e.g., Cushway, 1992;Cushway & Tyler, 1994;Galvin & Smith, 2015;Kaeding et al, 2017;Kuyken, Peters, Power & Lavender, 1998;Vredenburgh et al, 1999). Longitudinal studies are important with clinical psychology trainees and, generally, with clinical psychologists (McCormack et al, 2018), because cross-sectional studies only show a static picture of the situation.…”
Section: Palabras Clavementioning
confidence: 89%
“…Síntomas emocionales, depresión, estrés, practicantes en psicología clínica, estudiantes universitarios Training in clinical psychology usually involves intensive theoretical and practical work, guided by a clinical supervisor, and it is broadly acknowledged as a stressful experience (e.g., Cartwright & Gardner, 2016;Kaeding et al, 2017;Volpe et al, 2014). Specifically, clinical psychology trainees often face stressors such as dealing with patients' suffering, lack of time, financial issues, self-doubts, poor supervision, academic and research workload, perceived competition between colleagues, or attending to patients with severe suicidal ideation (e.g., Cushway, 1992;El-Ghoroury, Galper, Sawaqdeh, & Bufka, 2012;Galvin & Smith, 2015;Hill, Sullivan, Knox, & Schlosser, 2007).…”
Section: Palabras Clavementioning
confidence: 99%
“…Originally, burnout was investigated among helping professionals such as nurses, psychologists and physicians and among educational staff, mostly teachers (for review see National Academy of Medicine 2019; Kaeding et al 2017). School psychologists are trained in a variety of treatment and diagnostic methods in order to provide services to a range of educational settings.…”
Section: Burnout Among School Psychologistsmentioning
confidence: 99%